2000
DOI: 10.1590/s1413-95962000000300008
|View full text |Cite
|
Sign up to set email alerts
|

Variações fisiológicas de parâmetros reprodutivos em vacas de raça Holandesa importadas da Hungria para o Nordeste brasileiro

Abstract: c-quadrado e teste t. O período de aclimatação influencia negativamente a eficiência do tratamento de superovulação e produção de embriões. Com isso, o número de ovulações (6,7 ± 3,5) e de embriões de boa qualidade (1,2 ± 0,5), a eficiência de coleção (57,0%) e a proporção de obtenção de embriões (46,3%) foram significativamente diferentes do grupo testemunha. Durante o período de aclimatação de um ano e meio, a alta temperatura contínua e as horas claras permanentes parecem adversamente afetar as respostas da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies carried out by Bényei and Barros [28] demonstrated that exposure to stress in dairy cows during summer or in a hyperthermic environmental chamber (42˚C) during 7 days reduced the viability of embryos collected and increased the incidence of degenerated embryos and late development. In this study we had the same observations in EG 2 and EG 3 groups, in other words, formation of asymmetric divisions, embryos in the process of degeneration and developmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out by Bényei and Barros [28] demonstrated that exposure to stress in dairy cows during summer or in a hyperthermic environmental chamber (42˚C) during 7 days reduced the viability of embryos collected and increased the incidence of degenerated embryos and late development. In this study we had the same observations in EG 2 and EG 3 groups, in other words, formation of asymmetric divisions, embryos in the process of degeneration and developmental delay.…”
Section: Discussionmentioning
confidence: 99%